2011
DOI: 10.1111/j.1440-1584.2011.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality patterns of Australian male farmers and farm managers

Abstract: These data indicate that Australian male farmers and farm managers are a disadvantaged group in terms of health status. The elevated rates of all-cause and specific-cause mortality compared with the Australian comparison population, illustrate both the need and scope for further investigation of these issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 26 publications
0
28
1
Order By: Relevance
“…This is in contradiction with other authors [9,20] and can be explained by several reasons. One of the important contributors to CVD is smoking.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…This is in contradiction with other authors [9,20] and can be explained by several reasons. One of the important contributors to CVD is smoking.…”
Section: Discussioncontrasting
confidence: 97%
“…One of the challenges in interpreting these varied results is that farmers have mostly been compared with the general male population [5,9], or rural workers to urban workers, without comparing different occupational groups in the rural setting [2]. While prevalence rates for cardiovascular disease are worse in rural than urban Australia [10], there is a lack of published data on differences between occupations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that mechanisation in the agricultural sector might lead to increased sedentary behaviours among farmers. 2 Together, these observations highlight the need to understand links between occupation type and sedentariness, including prolonged sitting, in the work settings of rural men. The aim of this study was to compare objectively measured sedentary behaviours among rural Australian men in contrasting occupational settings, desk-based offices and on farms in the Riverland of South Australia.…”
Section: Introductionmentioning
confidence: 96%
“…1 Male Australian farmers are a particularly high-risk group, with a 40% higher rate of age-standardised deaths due to circulatory diseases compared with the general Australian male population. 2 Independent of physical activity, there is an elevated risk of adverse health outcomes associated with sedentary behaviour, particularly uninterrupted sitting. 3 Studies of office-based occupations have found that over 75% of the working day is spent sitting.…”
Section: Introductionmentioning
confidence: 99%
“…1 In this edition, the discussion by Fragar et al 2 of all cause mortality of male farmers and farm managers (farmers) in Australia is one such study. The finding appears simple: all cause mortality was 33% higher (1999)(2000)(2001)(2002) for farmers than for the Australian male population after appropriate standardization.…”
mentioning
confidence: 98%